2019
DOI: 10.1007/s00276-019-02298-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the dentate gyrus in normal adult brain

Abstract: Recent scientific papers indicate the clinical significance of the dentate gyrus. However, a detailed knowledge of the anatomical variations of this structure in normal adult brain is still lacking. An understanding of the variable morphology of the dentate gyrus may be important for diagnostic neuroimaging. Thus, the purpose of this macroscopic cadaveric study was to describe the anatomical variations of the dentate gyrus. Forty formalin-fixed human cerebral hemispheres, obtained from bodies of donors without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
5
1
1
Order By: Relevance
“…We chose to retain these categorical descriptions while changing the language to "well-de ned", "moderately de ned", and "illde ned". While previous results found that 67.5% were well-developed, 22.5% were underdeveloped, and 10% were hypoplastic, we found that 36% were well-de ned, 51% were moderately de ned, and 13% were ill-de ned [7]. Both ndings indicate that there is in fact variation in the qualitative scoring of the dentate gyrus, but there are some differences in the speci c results (e.g.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…We chose to retain these categorical descriptions while changing the language to "well-de ned", "moderately de ned", and "illde ned". While previous results found that 67.5% were well-developed, 22.5% were underdeveloped, and 10% were hypoplastic, we found that 36% were well-de ned, 51% were moderately de ned, and 13% were ill-de ned [7]. Both ndings indicate that there is in fact variation in the qualitative scoring of the dentate gyrus, but there are some differences in the speci c results (e.g.…”
Section: Discussioncontrasting
confidence: 90%
“…One potential cause for this could be the hemispheres utilized. Haladaj reported the use of forty hemispheres but did not indicate if those were left, right, or both sides [7]. Given that this study utilized both this could be a potential cause for varying results.…”
Section: Discussionmentioning
confidence: 91%
“…If the goal is to postulate about the function of specific brain regions, inferring the sought activity requires knowledge about the underlying brain structures and the exact electrode locations. However, subject brain and general anatomical characteristics present a significant variability (Bartley et al, 1997 ; Yang et al, 2019 ; Haładaj, 2020 ). Individual head shapes also cause differences in the relative placement and studies show that the considered electrode locations can greatly affect analyses results (Schwartz et al, 1996 ; Van Hoey et al, 2000 ; Wang and Gotman, 2001 ; Dalal et al, 2014 ; Hirth et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…If the goal is to postulate about the function of specific brain regions, inferring the sought activity requires knowledge about the underlying brain structures and the exact electrode locations. However, subject brain and general anatomical characteristics present a significant variability (Haładaj, 2020; Yang et al, 2019; Bartley et al, 1997). Individual head shapes also cause differences in the relative placement and studies show that the considered electrode locations can greatly affect analyses results (Hirth et al, 2020; Van Hoey et al, 2000; Wang and Gotman, 2001; Dalal et al, 2014; Schwartz et al, 1996).…”
Section: Introductionmentioning
confidence: 99%